2014
DOI: 10.1016/j.mib.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

What can we learn from fitness landscapes?

Abstract: A combinatorially complete data set consists of studies of all possible combinations of a set of mutant sites in a gene or mutant alleles in a genome. Among the most robust conclusions from these studies is that epistasis between beneficial mutations often shows a pattern of diminishing returns, in which favorable mutations are less fit when combined than would be expected. Another robust inference is that the number of adaptive evolutionary paths is often limited to a relatively small fraction of the theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 47 publications
0
51
0
Order By: Relevance
“…falciparum parasites [67]. Furthermore, PfCRT mutations can be deleterious to parasite growth [16,42], a measurable phenotype that serves as a proxy for fitness and reflects parasite functional requirements [68]. To evaluate the contributions of Cam734-unique PfCRT mutations to parasite growth, we used previously established co-culture methods to derive relative growth estimates [16,69].…”
Section: Resultsmentioning
confidence: 99%
“…falciparum parasites [67]. Furthermore, PfCRT mutations can be deleterious to parasite growth [16,42], a measurable phenotype that serves as a proxy for fitness and reflects parasite functional requirements [68]. To evaluate the contributions of Cam734-unique PfCRT mutations to parasite growth, we used previously established co-culture methods to derive relative growth estimates [16,69].…”
Section: Resultsmentioning
confidence: 99%
“…This observation of two alternative residues in position V L Y50 raised the possibility of deleterious negative epistatic interactions454647 between these residues and other mutations and suggested a another possible driving force behind selection of either histidine or serine in this position. This bifurcation in the evolutionary history of the final variants48 would be indicative of a rugged fitness landscape4950.…”
Section: Resultsmentioning
confidence: 99%
“…Given this, we predict that the taxa that compose the gut microbiota might be similarly We found that higher-order interactions were present, and that taxa interacted both antagonistically (Hartl, 2014…”
mentioning
confidence: 90%